2013
DOI: 10.1177/1468087413501316
|View full text |Cite
|
Sign up to set email alerts
|

Size-scaling effect on the velocity field of an internal combustion engine, part II: Turbulence characteristics

Abstract: Top dead center turbulence characteristics in two geometrically scaled, two-valve, single-cylinder research engines were investigated to study engine size scaling relationships. Velocity data were acquired using high-magnification particle image velocimetry with different port geometries (two), different port orientations (two), and with both shrouded and nonshrouded intake valves. The data were analyzed using both an ensemble-average method and spatial-average method of defining the mean velocity field. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However the decomposition is based on the harmonic functions, in addition like most of turbulent flows, the choice of a cut-off frequency/length remains a complex subject [8,26]. In addition, various spatial filter techniques such as Gaussian kernel exist, which distinguish CCV from turbulent fluctuations [19,38]. However, the results depend again on the filter size.…”
Section: Introductionmentioning
confidence: 99%
“…However the decomposition is based on the harmonic functions, in addition like most of turbulent flows, the choice of a cut-off frequency/length remains a complex subject [8,26]. In addition, various spatial filter techniques such as Gaussian kernel exist, which distinguish CCV from turbulent fluctuations [19,38]. However, the results depend again on the filter size.…”
Section: Introductionmentioning
confidence: 99%
“…Although the similarity of engine performance and emissions can be achieved to some extent, as shown in the above literature review, the existing three scaling laws exhibit several weaknesses that should be further addressed. For example, the brake thermal efficiency (BTE) is difficult to be completely scaled due to the increased heat transfer loss 18,19 and friction loss 20,21 of small engine caused by the larger surface to volume ratio. In the previous study, the intake temperatures of the small engines were usually increased to compensate for the effect of larger heat transfer losses.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the S rule is more preferable in the LTC regimes, due to the identical timescale for chemical reactions. Recently, Heim and colleagues 12,13 investigated the similarity of turbulence properties in different size engines. They found that the swirl center locations are in nearly the same location between the large and small engines.…”
Section: Introductionmentioning
confidence: 99%